Can neoadjuvant chemoradiotherapy combined with immunotherapy benefit patients with microsatellite stable locally advanced rectal cancer? a pooled and integration analysis - Yue, Yumin; Cheng, Min; Xi, Xiaohui; Wang, Quan; Wei, Mingtian; Zheng, Bobo (Frontiers in Oncology, 2023)
Objective To assess the clinical efficacy of neoadjuvant chemoradiotherapy combined with immunotherapy for patients with microsatellite stable (MSS) locally advanced rectal cancer and provide evidence to support clinical decision-making. Methods A systematic search was conducted on the PubMed, Embase, Cochrane Collaboration databases, conference summaries, and Chinese databases for clinical studies that investigated neoadjuvant chemoradiotherapy combined with immunotherapy for the treatment of locally advanced rectal cancer with MSS status. The search spanned from the inception of each database through July 2023. Data from the identified studies were extracted using a pre-designed table, and efficacy outcomes were analyzed. An integrated analysis was conducted using Stata 12.0 software. Results Eight studies were included, comprising 204 patients with locally advanced MSS rectal cancer who received chemoradiotherapy combined with immunotherapy. The integrated analysis revealed a pathologic complete remission rate of 0.33, a sphincter preservation rate of 0.86, an R0 resection rate of 0.83, a major pathologic remission rate of 0.33, and a clinical complete remission rate of 0.30. Conclusion Neoadjuvant chemoradiotherapy combined with immunotherapy demonstrates significant short-term efficacy in MSS-type locally advanced rectal cancer, notably enhancing the pathologic complete remission and sphincter preservation rates. This combination is a recommended treatment for patients with MSS-type rectal cancer.